2012
DOI: 10.1890/12-0133.1
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic noise is associated with reductions in the productivity of breeding Eastern Bluebirds (Sialia sialis)

Abstract: Although previous studies have related variations in environmental noise levels with alterations in communication behaviors of birds, little work has investigated the potential long-term implications of living or breeding in noisy habitats. However, noise has the potential to reduce fitness, both directly (because it is a physiological stressor) and indirectly (by masking important vocalizations and/or leading to behavioral changes). Here, we quantified acoustic conditions in active breeding territories of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 54 publications
0
71
1
Order By: Relevance
“…foraging behaviour, signalling characteristics, movement patterns) need more careful consideration because animals may be able to compensate in quieter periods, the implications of the behavioural change are unclear or there may be costs associated with the noiseinduced adjustment [14], and thus there may be no direct link between short-term effects and long-term consequences (see [67]). That is not to say changes in fitness do not result, but rather that the experiments required to determine them have rarely been carried out (but see [59,64,68,69]). A multiyear study by Francis et al [59] demonstrated that some species might actually gain from additional noise if, for instance, potential predators avoid the area, and thus implications for individual fitness and community structure are not necessarily easy to predict.…”
Section: (C) Need To Evaluate Effects Of Noise On Individual Fitnessmentioning
confidence: 99%
“…foraging behaviour, signalling characteristics, movement patterns) need more careful consideration because animals may be able to compensate in quieter periods, the implications of the behavioural change are unclear or there may be costs associated with the noiseinduced adjustment [14], and thus there may be no direct link between short-term effects and long-term consequences (see [67]). That is not to say changes in fitness do not result, but rather that the experiments required to determine them have rarely been carried out (but see [59,64,68,69]). A multiyear study by Francis et al [59] demonstrated that some species might actually gain from additional noise if, for instance, potential predators avoid the area, and thus implications for individual fitness and community structure are not necessarily easy to predict.…”
Section: (C) Need To Evaluate Effects Of Noise On Individual Fitnessmentioning
confidence: 99%
“…Previous research has demonstrated that increased noise can lead to decreased reproductive success (Halfwerk et al, 2011;Kight et al, 2012;Mulholland, 2016), impact community structure and ecological interactions (Francis et al, 2009), and degrade habitat quality (Francis et al, 2009;McClure et al, 2013;Ware et al, 2015). Most relevant to this study are the many ways that noise affects avian behavior (Shannon et al, 2016b), especially aspects of risk assessment and antipredator behavior.…”
mentioning
confidence: 99%
“…Several studies have found a reduced number of species or individuals with increasing noise (e.g., Rheindt 2003;Francis et al 2009;Blickley et al 2012;McClure et al 2013), and some studies have suggested a link between noise and reduced breeding success (Halfwerk et al 2011a;Kight et al 2012;Schroeder et al 2012). By masking the acoustic signals of birds, noise can impair communication and potentially interfere during social interactions (Brumm and Slabbekoorn 2005;Patricelli and Blickley 2006;Warren et al 2006;RĂ­os-ChelĂ©n 2009;Brumm and Zollinger 2013;Slabbekoorn 2013;Gil and Brumm 2014).…”
Section: Introductionmentioning
confidence: 99%